Interoperabilitas NDN-DPDK dan Forwarding NFD dalam Video Streaming berbasis NDN pada Virtual Machine - Syafaat Deha; Malldi Saesar; Syifa Aulia Sakira Nur Rahman; Anggita Yaumil Istiana; Leanna Vidya Yovita; Istikmal Istikmal; Tody Ariefianto Wibowo (Syntax Corporation, 2023)
The Named Data Network (NDN) is a future network concept that addresses some of the issues present in the current internet architecture. One of the main advantages of NDN is the use of content caching at each router, enabling faster and more efficient data access. As internet network technology develops, the demand for video content continues to increase every year. Therefore, video optimization and delivery require high access speeds so that clients can run content from the server seamlessly. This research incorporates NDN-DPDK (Named Data Network-DData Plane Development Kit), which is designed as hardware acceleration, and uses NDN's default forwarder, Network Forwarding Daemon (NFD), which allows a wide variety of experiments with NDN architecture. The implementation and analysis of video streaming performance will use Quality of Service (QoS) parameters such as RTT, throughput, and startup delay to measure the quality of video streaming on the network side. In addition, CPU measurements are made on the router closest to the client to evaluate the traffic load required by the forwarder to transmit data. The results of implementation and analysis in this study obtained video streaming quality on the second accessor with an RTT time of 4 seconds, throughput above 0.4 MBps, a video startup delay of 8 seconds, and 100% CPU usage.